Influence of different percentages of water reuse with bioflocs on the composition of the microbiota in the stomach of Penaeus vannamei shrimp - Natália Pereira San Martin; Wilson Wasielesky, Jr.; Francesca Cucchi; Wellica Gomes dos Reis; Dariano Krummenauer (Aquaculture and Fisheries)
The objective of this study was to analyze the stomach composition of Penaeus vannamei shrimp in biofloc cultures with varying percentages of reused bioflocs to identify the optimal culture conditions based on microorganism content. Four treatments were employed: clear water (CW), 25% biofloc inoculum (BF 25%), 50% biofloc inoculum (BF 50%), and 100% biofloc inoculum (BF 100%). Bioflocs were reused from mature bioflocs of previous cultures in biofloc treatments. Shrimp performance was monitored weekly through biometrics, and stomach samples were collected at the experiment's onset and conclusion. The samples underwent fixation in 4% formaldehyde for subsequent counting and identification of predominant microorganism groups using an inverted microscope. Bacterial abundance was assessed by fixing, filtering, and staining samples with acridine orange, followed by quantification with an epifluorescence microscope. Water quality parameters remained satisfactory in all treatments. Shrimp stomachs in biofloc systems contained Oocystis sp., ciliates, flagellates, diatoms, free coccoids, free and attached filamentous, Bacillus spp., and Vibrio spp. CW treatment exhibited the highest Vibrio spp. concentration. Overall, reusing bioflocs in all volume percentages effectively maintained water quality and colonized the animal's microbiota, with a recommended minimum reuse percentage of 25% for satisfactory results.